The complete mitochondrial genome of the seed-borer weevil, Bruchidius uberatus (Coleoptera: Chrysomelidae: Bruchinae). Issue 1 (2nd January 2020) - Zhang, Li-Jie; Wu, Ling; Li, You; Li, Jian-Guang; Yang, Xing-Ke; Nie, Rui-E
Abstract: In this study, the complete 15, 892 bp mitochondrial genome of Bruchidius uberatus (Fåhraeus) was sequenced using Illumina NovaSeq6000 platform. The mitogenome is a double-stranded circular molecule of 15, 892 bp in length with 22 transfer RNA genes, 13 protein-coding genes and two ribosomal RNA genes as in other insects. Twenty-five species from 8 subfamilies of Chrysomelidae were selected as ingroups and 3 species of Lamiinae as outgroups for phylogenetic analysis based on mitogenome. The results showed that the subfamily Bruchinae was monophyly. Genus Bruchidius had more closed relationship with Acanthoscelides than Callosobruchus in Bruchinae with high support values.